Organisational design of a university’s social mission: a functional approach - Volnistaya, Marina G. (Journal of the Belarusian State University. Sociology, 2022)
In the article author considers the theory of organisational design in relation to the study of new adaptive properties of university education, altered especially by the conditions of COVID‑19. The analysed concerns content of methodological approaches and principles of organisational design of functional structure of university education. Author considers the role of the goal-setting and strategic management stage of the university in modern conditions and compares the system-functional and system-targeted approaches to the organisational design of the university mission. The functional content of the strategy allowing full realisation of competitive advantages of universities in the global market of educational services is considered.